DEVELOPING TERMINOLOGICAL COMPETENCE IN A SPECIALIZED TRANSLATION (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This article examines the development of terminological competence in specialized translation classrooms, focusing on the challenges faced by both students and educators, as well as the resources and tools available to support this process. Terminological competence, a critical skill for translators working in specialized fields such as law, medicine, and technology, involves not only the accurate understanding and use of specialized terms but also the ability to apply them in context. The article highlights key problems, including the rapid evolution of terminology, the complexity of subject-specific language, and the vast amount of knowledge required to master specialized terminology.